The Effect of Diabetes Mellites Type 2 on the Cholelithiasis Patients - Japer, Farajalmuntadhr M; Mohammed, Nidhal Y.; Alhilfi, Wissal A. (Migration Letters, 2023)
Back ground: Diabetes mellitus, is a syndrome that is characterized by hyperglycemia, it is one of the most common world’s diseases, diabetes imposes different burdens due to the various complications associated with (Omoruyi et al., 2021).The current evidence has suggested that, the diabetes mellitus is associated with the gallstone’s development, this could be attributable to the impaired of gallbladder emptying and a decreasing in secretion of bile salt from the gallbladder (C.-H. Chen et al., 2018). Aim: Study the effect of Diabetes on gallstones patients, as it is responsible for hyperglycemia, increasing triglycerides and gallstones diseases. Results: All biochemical markers, demonstrate highly significant difference (p < 0.05) compared to the control group as a total number and as males and females’ groups separately, except for (I. R) in males’ group. The same significant behavior was found when comparing both gender with each another, except for (BMI, HbA1C, ALP & bilirubin). The (ROC) curve for gallstones patients shows: All biomarkers show high significant statistical behavior and high % of area under the curve, with a good characteristic of validity for tests, except the validity characteristic for (BMI) for both genders, insulin for female and (I. R & GGT) for males. Spearman’s nonparametric statistical correlation shows: Different positive and negative correlations coefficient for biomarkers, as the table showed. Conclusion: The results obtained concluded that overweight, insulin resistance, and high levels of leptin, which all indicate the metabolic syndrome, are the main contributors to the formation of gallstones. Abbreviations used: BMI: Body mass index, FBS: Fasting blood sugar, HbA1C: Hemoglobin A1 C, I. R: Insulin resistance, CRP: C-reactive protein, ALP: alkaline phosphatase, GGT: gamma-glutamyl Transferase, ROC: receiver operating characteristic, GD: gallstones disease and (MetS): Metabolic syndrome.